Installation art as a trace of the artistic process - Sztabińska-Kałowska, Paulina (Ars inspiratio: Studies dedicated to Professor Eleonora Jedlińska, 2024)
In the article I focus on considering installation art as a trace of the artistic process. This issue appeared clearly in connection with action painting and the work of Jackson Pollock. Art critics pointed out that in the case of the American artist’s paintings, making a painting was no longer the goal of his actions. What was presented to the public was a painting, i.e. a surface covered with color spots. However, the properties of this product clearly suggested the need to take into account the activities that led to its creation, and to take into account the painting technique used by Pollock called dripping. Later, in the 1950s and 1960s, this tendency was developed in happenings and events. Happening theorists pointed to action painting as one of the sources of this creativity. The possibility of transforming a happening into an installation and vice versa was included in the concept of both artistic phenomena from the very beginning. Also in performance art, the „remains” of the artist’s actions are often treated as objects or installations. In the article I will discuss examples of the activities of artists (including Allan Kaprow, Joseph Beuys, Marcin Berdyszak, Julian H. Raczko, and others), for whom the created installations are a record of their activities, a kind of trace of themselves.